Czech Republic: An Open Market Dominated by Large Owners - Leichmann, Jan; Vomáčka, Vojtěch (Acquisition of Agricultural Lands, 2022)
This chapter focuses on the acquisition of agricultural land in the Czech Republic. It aims to describe this topic in its historical and property law context since the privatization of agricultural land after 1989 still concerns its transfer from the state to private individuals. Furthermore, transfers of agricultural land were restricted on the basis of nationality until being gradually abolished after the Czech Republic joined the European Union in 2004. First, the chapter describes the Czech concept of agriculture and agricultural land and the general legal framework of both protection and transfer of agricultural land. Then, restrictions on the cross-border acquisition of agricultural land are analyzed in the context of land restitution and specific measures toward foreign investors. A separate subchapter is devoted to the application of the preemption right of the state. The last part introduces the general requirements on the transfer of agricultural land, with a particular focus on the evidence in the Real Estate Register. Additionalrequirements for the transfer of state-owned land are described with details on priority transfers of agricultural land, sales by public offer, and public tender. The authors conclude that, currently, the only major obstacle to the cross-border acquisition of agricultural land in the Czech Republic is the state’s preemption right, which applies only to selected land, particularly in protected natural areas. Transfers of state-owned agricultural land are governed by special rules, which, however, do not in principle restrict interested parties from other states within the EU or the European Economic Area. Neither do they distinguish between persons residing or established in the Czech Republic and in another member state, nor do they differentiate between the requirements for conducting agricultural activities.Keywords: Czech land law, acquisition of land, agricultural land, restitution, preemptive right